A common UCP2 polymorphism predisposes to stress hyperglycaemia in severe sepsis. Issue 11 (25th June 2009) - Pyle, A; Ibbett, I M; Gordon, C; Keers, S M; Walker, M; Chinnery, P F; Baudouin, S V
Abstract : Background: Insulin resistance and hyperglycaemia are common in severe sepsis. Mitochondrial uncoupling protein 2 (UCP2) plays a role in insulin release and sensitivity. Objectives: To determine if a common, functional polymorphism in the UCP2 gene promoter region (the −866 G/A polymorphism) contributes to the risk of hyperglycaemia in severe sepsis. Results: In the prospective group 120 non-diabetic patients who were carriers of the G allele had significantly higher maximum blood glucose recordings than non-carriers (mean (SD) AA 8.5 (2.2) mmol/l; GA 8.5 (2.4) mmol/l; GG 10.1 (3.1) mmol/l; p = 0.0042) and required significantly more insulin to maintain target blood glucose (p = 0.0007). In the retrospective study 103 non-diabetic patients showed a similar relationship between maximum glucose and UCP genotype (AA 6.8 (2.3) mmol/l; GA 7.8 (2.2) mmol/l; GG 9.2 (2.9) mmol/l; p = 0.0078). Conclusions: A common, functional polymorphism in the promoter region of the UCP2 gene is associated with hyperglycaemia and insulin resistance in severe sepsis. This has implications for our understanding of the genetic pathophysiology of sepsis and is of use in the stratification of patients for more intensive management.